Allpanchis, its readers and writers - Caro Cárdenas, Ricardo (2005)
In an issue dedicated to reading, the Allpanchis management wanted to collect the perception of its readers and summoned three of them, among other reasons for their interest in contributing their time and talent in this new stage of the magazine. Ricardo Caro, Osmas Gonzales and Javier Torres are readers and also writers for Allpanchis and other media. Thus, they met with Félix Grández to review the magazine's itinerary and outline the elements that will define the characteristics of the magazine's next stage.